t(5t+2)=

Simple and best practice solution for t(5t+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for t(5t+2)= equation:


Simplifying
t(5t + 2) = 0

Reorder the terms:
t(2 + 5t) = 0
(2 * t + 5t * t) = 0
(2t + 5t2) = 0

Solving
2t + 5t2 = 0

Solving for variable 't'.

Factor out the Greatest Common Factor (GCF), 't'.
t(2 + 5t) = 0

Subproblem 1

Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0

Subproblem 2

Set the factor '(2 + 5t)' equal to zero and attempt to solve: Simplifying 2 + 5t = 0 Solving 2 + 5t = 0 Move all terms containing t to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5t = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5t = 0 + -2 5t = 0 + -2 Combine like terms: 0 + -2 = -2 5t = -2 Divide each side by '5'. t = -0.4 Simplifying t = -0.4

Solution

t = {0, -0.4}

See similar equations:

| 276/12 | | Y=6x^2+x-15 | | -(-21y+29)-21y=-(19y+23)+26 | | 4m+6m+7m= | | 81w^2-49= | | -(67r+8s+61)= | | 5(3-y)/3=y-5 | | X^2-13x-168= | | 2x-1=y+4 | | 16-5(3p-4)=8(-2p+11) | | 9=3(5q-2) | | -6x+3(3)= | | X+8=4(X-10) | | -4x-6=-42 | | x/2-5=6 | | (1/3)x=1017 | | 120+x^2-200+11x=100 | | 2x+2=3x-ray | | x^2-14x=-53 | | 120+x^2-200+11x=P | | -4x-6=22 | | 3(x-7)+2=12x-3 | | x^4=-81x^2 | | 12-8y=13 | | 6x=2(2x-3) | | (1/4)x=866 | | 8k-1=23-k-3k | | -12x^2-7x+10=0 | | 54-3x=6x+9 | | (-4.5)= | | f/-3+2=6 | | 3x+6=28 |

Equations solver categories